Adubação com potássio e cálcio na nutrição e produção de goiabeira ‘Paluma’ - Pereira Cavalcante, Alian Cássio; Ferreira Cavalcante, Lourival; Pereira Bertino, Antonio Michael; Guilherme Cavalcante, Adailza; de Lima Neto, Antonio João; Ferreira, Nubia Marisa (Revista Ceres, 2025)
The guava is a fruit cultivated worldwide, distinguished by the great acceptance in the consumer market. However, so that the crop exploits its maximum productive potential and maintains the quality of the fruits it is necessary an adequate mineral fertilization to raise the availability of nutrients in the soil and to increase the absorption by plants. The objective of the work was to evaluate the effects of fertilization with potassium doses, in the presence and absence of calcium, on the nutritional status and on the production of ‘Paluma’ guava. The experiment was carried out from August 2015 to May 2016, in the municipality of Remígio-PB, Brazil. The variables analyzed were: macro and micronutrient leaf contents, number of fruits per plant, average fruit mass, fruit yield per plant and productivity. Guava plants were adequately supplied with nitrogen, phosphorus, potassium, calcium, magnesium, boron, iron and manganese, and deficient in sulfur, copper and zinc. Calcium fertilization increased the leaf content of P, K, Ca, S, B, Mn and Zn, but reduced the number of fruits per plant and the yield of ‘Paluma’ guava. Potassium fertilization without calcium addition at doses between 101 and 143 g plant-1 year-1 K2O at 16 months of age provides the highest productivity of ‘Paluma’ guava.